Political Skill and Work Outcomes: A Theoretical Extension, Meta‐Analytic Investigation, and Agenda for the Future. Issue 1 (13th January 2014) - Munyon, Timothy P.; Summers, James K.; Thompson, Katina M.; Ferris, Gerald R.
<x xml:space="preserve">Abstract</x> This quantitative review explored the political skill construct and its predictive ability across a number of organizational outcomes. First, we extended the Ferris et al. meta‐theoretical framework of political skill. Next, incorporating meta‐analysis, we found political skill is positively related to self‐efficacy, job satisfaction, organizational commitment, work productivity, organizational citizenship behavior (OCB), career success, and personal reputation, and negatively related to physiological strain. Political skill was not significantly related to psychological strain or perceptions of organizational politics. Using meta‐regression and dominance analyses, political skill predicted task performance after controlling for the Big Five personality characteristics and general mental ability. In a test of indirect relationships, our results suggest that personal reputation and self‐efficacy partially mediate the political skill–task performance relationship. Finally, in a post hoc test of political skill dimensions, we found that networking ability, interpersonal influence, and apparent sincerity (but not social astuteness) predicted task performance. Our findings provide a comprehensive assessment of theory and research to date on political skill and extend theoretical foundations to stimulate new inquiry into the operation of this important construct.